Zinc Oxide and Magnesium-Doped Zinc Oxide Nanoparticles Ameliorate Murine Chronic Toxoplasmosis - Mohamed H. Sarhan; Shatha G. Felemban; Walla Alelwani; Hesham M. Sharaf; Yasmin A. Abd El-Latif; Elsayed Elgazzar; Ahmad M. Kandil; Guillermo Tellez-Isaias; Aya A. Mohamed (Pharmaceuticals, 2024)
Toxoplasma gondii causes a global parasitic disease. Therapeutic options for eradicating toxoplasmosis are limited. In this study, ZnO and Mg-doped ZnO NPs were prepared, and their structural and morphological chrematistics were investigated. The XRD pattern revealed that Mg-doped ZnO NPs have weak crystallinity and a small crystallite size. FTIR and XPS analyses confirmed the integration of Mg ions into the ZnO framework, producing the high-purity Mg-doped ZnO nanocomposite. TEM micrographs determined the particle size of un-doped ZnO in the range of 29 nm, reduced to 23 nm with Mg2+ replacements. ZnO and Mg-doped ZnO NPs significantly decreased the number of brain cysts (p < 0.05) by 29.30% and 35.08%, respectively, compared to the infected untreated group. The administration of ZnO and Mg-doped ZnO NPs revealed a marked histopathological improvement in the brain, liver, and spleen. Furthermore, ZnO and Mg-doped ZnO NPs reduced P53 expression in the cerebral tissue while inducing CD31 expression, which indicated a protective effect against the infection-induced apoptosis and the restoration of balance between free radicals and antioxidant defense activity. In conclusion, the study proved these nanoparticles have antiparasitic, antiapoptotic, and angiogenetic effects. Being nontoxic compounds, these nanoparticles could be promising adjuvants in treating chronic toxoplasmosis.